Leukocyte telomere length in patients with myotonic dystrophy type I: a pilot study. Issue 1 (5th December 2019) - Wang, Youjin; Best, Ana; Fernández‐Torrón, Roberto; Alsaggaf, Rotana; Garcia‐Puga, Mikel; Dagnall, Casey L.; Hicks, Belynda; Thompson, Mone't; Matheu Fernandez, Ander; Zulaica Ijurco, Miren; Greene, Mark H.; Lopez de Munain, Adolfo; et al.
Abstract: Myotonic dystrophy type I (DM1) is an autosomal dominant disease of which clinical manifestations resemble premature aging. We evaluated the contribution of telomere length in pathogenesis in 361 DM1 patients (12 with serial measurements) and 223 unaffected relative controls using qPCR assay. While no differences in baseline leukocyte relative telomere length (RTL) was noted, the data suggested an accelerated RTL attrition in DM1 (discovery cohort: T/S change/year = −0.013 in DM1 vs. −0.005 in controls, P  = 0.04); similar trend was noted in validation cohort. Further investigations are needed to examine the role of TL in the pathophysiology of DM1.